1988
DOI: 10.1073/pnas.85.17.6566
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-releasing hormone-induced Ca2+ transients in single identified gonadotropes require both intracellular Ca2+ mobilization and Ca2+ influx.

Abstract: We examIned the effects of gonadotropinreleasing hormone (GnRH) (10). We now report the use of these techniques to show that GnRH produces Ca2" transients in identified gonadotropes with a very characteristic and complex time course. The role of these transients in the control of gonadotropin release is discussed. MATERIALS AND METHODSCell Culture. Female 35-day-old Sprague-Dawley rats were decapitated, their pituitaries were removed, and adenohypophyses were dissected from neurohypophyses. Anterior pituita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(23 citation statements)
references
References 31 publications
(38 reference statements)
3
20
0
Order By: Relevance
“…Some authors, however, do not agree [ 18]. Recently our group has confirmed the implica tion of PKC in the action of GnRH, but this effect was related to treatment of the cells by E2 [19,20], It has also been demonstrated that binding of GnRH to its receptor results in an increase in intracellular calcium ([Ca2 + ]i), which initiates events such as hormone secretion [21,22], This has been confirmed more recently by several studies using fluorescence analysis on gonadotroph populations [23][24][25] or in single gonadotroph cells [26][27][28][29]. Also, GnRH-induced [Ca2 + ]i increase was greater when cells were treated by E2 and this increase was affected by extra cellular calcium [30], [Ca2 + ]i increase in gonadotroph cells occurs through two major mechanisms: (i) mobilization of Ca2+ from in tracellular bound stores [10,31] and (ii) the influx of cal cium [32] across the plasma membrane via the voltagesensitive calcium channels (VSCC).…”
supporting
confidence: 52%
“…Some authors, however, do not agree [ 18]. Recently our group has confirmed the implica tion of PKC in the action of GnRH, but this effect was related to treatment of the cells by E2 [19,20], It has also been demonstrated that binding of GnRH to its receptor results in an increase in intracellular calcium ([Ca2 + ]i), which initiates events such as hormone secretion [21,22], This has been confirmed more recently by several studies using fluorescence analysis on gonadotroph populations [23][24][25] or in single gonadotroph cells [26][27][28][29]. Also, GnRH-induced [Ca2 + ]i increase was greater when cells were treated by E2 and this increase was affected by extra cellular calcium [30], [Ca2 + ]i increase in gonadotroph cells occurs through two major mechanisms: (i) mobilization of Ca2+ from in tracellular bound stores [10,31] and (ii) the influx of cal cium [32] across the plasma membrane via the voltagesensitive calcium channels (VSCC).…”
supporting
confidence: 52%
“…] c and hormone release (15,20,22,29). To quantify the responses to the HRHs, we measured the changes of [Ca 2ϩ ] c induced in the different cell types.…”
Section: Stimulation Of Hrh Receptors Induces An Increase Of [Ca 2ϩmentioning
confidence: 99%
“…Thus, Ca2+ channels could be activated by protein kinases and inactivated by phosphatases (19,22). GnRH receptors are coupled to the phospholipase C pathway and activation of protein kinase C, which could promote phosphorylation of L-type channels as suggested by the ability of phorbol esters to stimulate LH release and modulate Ca2' entry in gonadotrophs (23,24).…”
Section: Introductionmentioning
confidence: 99%